Efficacy Analysis of Day Surgery A1 Pulley Release for Pediatric Trigger Thumb - Linhua, Yan; Linjun, Jiang; Xiangyang, Qu; Xing, Liu; Ming, Li; Jun, Wu (Frontiers in Pediatrics, 2021)
Objective To investigate clinical application of day surgery A1 pulley release for pediatric trigger thumb. Methods We retrospectively analyzed the clinical data of 1642 children with trigger thumb who were treated with day surgery A1 pulley release at our hospital, including satisfaction surveys, functional recovery, and complications. Results The operative time for unilateral and bilateral tenolysis was 4.8±3.1 minutes and 9.2±3.8 minutes, respectively. Three children had postoperative fever and were discharged on the second day after surgery. The rest of the children were discharged on the day of surgery. All incisions healed primarily, and no complications of vascular and nerve injury were reported. The patients' degree of satisfaction with the medical treatment process, diagnosis and treatment workflow, treatment effectiveness, length of hospital stay and hospitalization cost, and discharge guidance were 97.9%, 96.1%, 99.3%, 91.1%, and 98.5%, respectively. The follow-up period was between 5 months and 3 years and 1 month. Four children experienced symptom relapse after the operation, and re-tenolysis was performed in one of them. At the final follow-up, the appearance and function of the thumb had recovered well in all cases. Conclusion Day surgery A1 pulley release can effectively release tendon sheaths and has a short operative time, no complications of vascular and nerve injury, and good recovery of thumb function. It is a safe and reliable procedure with high patient satisfaction, and it is worthy of clinical promotion.